QAWA'ÍD FIQHIYYAH DAN TANTANGAN ZAMAN: ANALISIS KONTEKSTUALITAS DAN PERAN QAWA'ÍD FIQHIYYAH DALAM SOLUSI PROBLEMATIKA HUKUM ISLAM - Ansori Ansori (IAIN Purwokerto, 2013)
The lack of religious texts in giving legal certainty to the various issues that always comes along with the rapid changes taking place in the midst of society make the ulamas strive to develop methodological tools that can be used to formulate laws. One of the the methodological devices is Qawaid Fighiyyah, which is the development of the Islamic jurisprudence approach. Islamic jurisprudence approach is already very long dominating the construction of Islamic legal thought. However, because its use is complicated and it needs a qualified skill, then it is more widely used by people who truly experts in various Islamic disciplines. While Qawaid Fighiyyah, because it is simple and has a wide cover, is more widely used by Muslims. It is increasingly visible in the contemporary era, where a lot of new problems arise and require immediate legal certainty. This research will discuss the contextual values of Qawaid Fighiyyah and the ability of Qawaid Fighiyyah to respond and provide solutions to various problems faced by Muslims.